2023
DOI: 10.1111/acer.15088
|View full text |Cite
|
Sign up to set email alerts
|

The role of culture in the association between racial discrimination and alcohol use among North American Indigenous adolescents reporting recent drinking

Abstract: Background: North American Indigenous (NAI) communities have identified alcohol use as a primary health concern. Experiences of racial discrimination are associated with greater alcohol use, but findings are mixed regarding the role of culture in this relationship. The goal of the present study was to examine the role of culture in the association between racial discrimination and alcohol use. Methods: Across two studies (Study 1: N = 52; Study 2: N = 1743), NAI adolescents living on or near NAI reservations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This finding provides further support for calls within the field to develop culturally‐specific measures (Greenfield et al, 2015), which may better represent Indigenous values and beliefs about health and well‐being, and for rigorous psychometric testing and potential adaptation of these measures. Finally, future research should include other factors that have been found to be related to racial discrimination, positive psychological characteristics, and school outcomes among NAI adolescents, such as parental racial socialization (Yasui et al, 2015), cultural identity (Schick et al, 2023; Schick, Nalven, et al, 2021), and mental health symptomatology (Tyser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides further support for calls within the field to develop culturally‐specific measures (Greenfield et al, 2015), which may better represent Indigenous values and beliefs about health and well‐being, and for rigorous psychometric testing and potential adaptation of these measures. Finally, future research should include other factors that have been found to be related to racial discrimination, positive psychological characteristics, and school outcomes among NAI adolescents, such as parental racial socialization (Yasui et al, 2015), cultural identity (Schick et al, 2023; Schick, Nalven, et al, 2021), and mental health symptomatology (Tyser et al, 2014).…”
Section: Discussionmentioning
confidence: 99%